PENGARUH JABATAN TERHADAP PERLAKUAN PENANGANAN KASUS PIDANA - Dwi Anggun Pratiwi; Erdianto Erdianto; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
A criminal act is an act that is prohibited by a rule of law, in which this prohibitionis accompanied by threats (sanctions) in the form of certain penalties for anyone whoviolates the prohibition. Criminal responsibility is a legal responsibility imposed onsomeone for mistakes or consequences of their actions. personally. Related to the subjectof crime needs to be explained, criminal responsibility is personal. That is, whoevercommits a crime, he must be held responsible, as long as in that person there is no basisfor abolishing the crime. The problem of law enforcement morality from time to time isstill a relevant issue to be discussed, because what is presented by the mass media isoften paradoxical.The type of research used in this research is normative legal research. In thisnormative study, law is conceptualized as what is written in statutory regulations or rulesor norms which are standards of human behavior that are considered appropriate. Incollecting this data using normative legal research techniques (legal research) usedmethods of literature review or documentary studies. Literature study is a data collectiontechnique by conducting a review study of books, literature, records and regarding casesthat occurred based on the problems above. Library materials can be either primary orsecondary materialsThe author concludes that the influence of position on the treatment of criminalcase handling is how the nature of law enforcement professionalism which in a generalsense means the ability and ability of a person to carry out a task because it is supportedby skills and expertise. Legal action against positions resulting in the handling ofcriminal cases in Indonesia is an abuse of authority and a violation of the code of ethicsof the legal profession, so that all legal professionals who are proven to have violated thecode of ethics of their profession can be followed up according to their profession. Inaddition, the author also provides suggestions, namely: There is a need for functionalcooperation between law enforcement agencies to conduct training for law enforcementofficials and whatever happens, the legal process remains in accordance with what hasbeen promulgated and in accordance with the procedures..Keywords: Accountability, Crime, Position.